2014
DOI: 10.2340/16501977-1272
|View full text |Cite
|
Sign up to set email alerts
|

Perceived usability and use of custom-made footwear in diabetic patients at high risk for foot ulceration

Abstract: Perceived usability of footwear was mostly positive, although individual scores and priorities varied considerably. Footwear use was low to moderate and dependent only on the perceived benefit of the footwear. Therefore, practitioners should focus on enhancing the patient's ap-preciation of the therapeutic benefit of custom-made footwear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 24 publications
5
88
1
5
Order By: Relevance
“…Одним из факторов, определяющих приверженность к ортопедической обуви, является возраст: чем старше пациент, тем он менее требователен к ортопедической обуви практически по всем параметрам ее оценки [17]. В нашем исследовании отмечена та же возрастная зави-симость.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Одним из факторов, определяющих приверженность к ортопедической обуви, является возраст: чем старше пациент, тем он менее требователен к ортопедической обуви практически по всем параметрам ее оценки [17]. В нашем исследовании отмечена та же возрастная зави-симость.…”
Section: Discussionunclassified
“…В нашей работе критерии определения той или иной степени тяжести деформаций были близки к таковым в работе Arts M. et al [17].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It starts from the moment a problem is reported, defines the design phase and concludes with the evaluation of the medical device and its use that has been supplied. Therefore, the key question is: Why there still remain -despite the use of ICF and PDMD -a substantial level of non-use of devices and a significant level of dissatisfaction among AFO users [6,14,15,17,[29][30][31]? In our opinion, the answer has to be found in the general character of the ICF and the PMDM that they neither facilitate a systematic and detailed analysis of the activities of users nor support a systematic mapping of the environments in which users are living.…”
Section: Identifying Needs Of Customersmentioning
confidence: 99%
“…In a qualitative study regarding diabetic therapeutic footwear, Johnson et al [53] noted a key finding was that patients and health professionals had differing perspectives in terms of expectations and reality of preventive behavior. Research has found an association between perceived benefit of diabetic shoes and adherent use of the shoes [54], suggesting improved education may have a role to play in improving adherence. Although a number of individual studies have reported style, perceived benefit, and other factors to be predictive of diabetic shoe adherence, a 2016 systematic review concluded that there are presently too few studies to draw any definitive conclusions [55].…”
Section: Optimizing User Experiencementioning
confidence: 99%